Crisis Interventions in Schools: A Systematic Review. (3rd April 2021) - Sokol, Rebeccah L; Heinze, Justin; Doan, Jessica; Normand, Meg; Grodzinski, Alison; Pomerantz, Naomi; Scott, Briana A; Gaswirth, Maura; Zimmerman, Marc
ABSTRACT: This systematic review synthesizes research on school-based crisis intervention protocols, descriptions, and evaluations. We performed a comprehensive literature search, and 60 studies met the inclusion criteria for this review. We found an overwhelming lack of evaluation studies (n = 3), suggesting that interventions are being administered post-crises without evaluation. The most frequently named crisis intervention model was the Prevent/Prepare, Reaffirm, Evaluate, Provide and Respond, and Examine (PREPaRE) model (n = 6). All evaluation studies in the sample were observational, and most adopted qualitative methods of evaluation. Future studies are needed to evaluate crisis interventions to measure the fidelity, reliability, and effectiveness of such interventions.